Comprehensive fluorogenic derivatization–liquid chromatography/tandem mass spectrometry proteomic analysis of colorectal cancer cell to identify biomarker candidate. (19th September 2012) - Koshiyama, Akiyo; Ichibangase, Tomoko; Imai, Kazuhiro
ABSTRACT Existing colorectal cancer biomarkers are insufficient for providing a quick and accurate diagnosis, which is critical for a good prognosis. More appropriate biomarkers are thus needed. To identify new colorectal cancer biomarker candidates, we conducted a comprehensive differential proteomic analysis of six cancer cell lines and a normal cell line, utilizing a fluorogenic derivatization–liquid chromatography–tandem mass spectrometry (FD‐LC‐MS/MS) approach. Two sets of intracellular biomarker candidates were identified: one for colorectal cancer, and the other for metastatic colorectal cancer. Our results suggest that cooperative expression of FABP5 and cyclophilin A might be linked to Her2 signaling. Upregulation of LDHB and downregulation of GAPDH suggest the existence of a specific nonglycolytic energy production pathway in metastatic colorectal cancer cells. Downregulation of 14‐3‐3ζ/δ, cystatin‐B, Ran and thioredoxin could be a result of their secretion, which then stimulates metastasis via activity in the sera and ascitic fluids. We propose a possible flow scheme to describe the dynamics of protein expression in colorectal cancer cells leading to tumor progression and metastasis via cell proliferation, angiogenesis, disorganization of actin filaments and epithelial–mesenchymal transition. Our results suggest that colorectal tumor progression may be regulated by signaling mediated by Her2, hypoxia, and TGFβ. Copyright © 2012 John Wiley & Sons, Ltd.